Drum drying process of jabuticaba pulp using corn starch as an additive - Nunes,Larissa Peixoto (2020)
Abstract Jabuticaba is a fruit native to Brazil, appreciated for its flavor and is also very nutritious, but it is a seasonal fruit and highly perishable. Therefore, drying is a good alternative for its conservation. The purpose of this work was to use drum drying to obtain jabuticaba flakes using corn starch as the main carrier agent. The sorption isotherm of the flakes at 25 °C was also studied, as well as the determination of the critical storage condition and the estimation of product shelf life through the permeability of different packages to the water vapor using mathematical models. The drum drying conditions were: temperature of 144 °C; residence time of 18 seconds; addition of 20% (dry basis) of corn starch and 0.5% (d.b.) of glyceryl monostearate. The final product was analyzed with respect to its physicochemical and technological properties. The sorption isotherm of the flakes was determined at 25 °C, using the gravimetric method with saturated solutions (0.11 ≤ aw ≤ 0.84). After the process, the flakes presented good retention of anthocyanins and total phenolic compounds, besides a high antioxidant activity. The water solubility of the product was around 70% and the hygroscopicity was approximately 24%. The equilibrium experimental points of the isotherm were better adjusted by the GAB model, with a monolayer moisture value of 12.74% (w.b) and a critical aw of 0.432.